2015
DOI: 10.1002/cbm.1969
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of offending trajectories in violent youth according to violence type

Abstract: The offending trajectories of young people with appetitively violent index offences were indistinguishable from other violent youths. There is thus insufficient information here to recommend distinctive intervention for this subgroup, but their high reoffending rate (7/9) suggests that they are worthy of more research attention. Copyright © 2015 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Follow‐up of participants considered their continued sanction for violence either within custody or the community. Although the sample sizes are small, the current 2‐year violent recidivism rate of 22% ( N = 2) compares favourably with studies indicating a 70% violence recidivism amongst young people (Ching et al ., ). Outcomes for custodial aggression are also positive, although there continued to be some sanctions for aggression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Follow‐up of participants considered their continued sanction for violence either within custody or the community. Although the sample sizes are small, the current 2‐year violent recidivism rate of 22% ( N = 2) compares favourably with studies indicating a 70% violence recidivism amongst young people (Ching et al ., ). Outcomes for custodial aggression are also positive, although there continued to be some sanctions for aggression.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, Ching et al . () reported that appetitive violent youths did not have a distinct offending trajectory compared with youths convicted of other violence. Rather, recent research has emphasized the importance of intervention addressing the core predictive risk factors for violence (Baglivio & Wolff, ; Miller‐Graff & Howell, ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations